PENGARUH KEGIATAN 3M TERHADAP KEMAMPUAN MOTORIK HALUS PADA ANAK USIA 5-6 TAHUN DI TK EDUCATION 21 KULIM KOTA PEKANBARU - Ori Lucia Fadella; Zulkifli '; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on the result of observation in the field toward fine motor skill ofstudent, it find that fine motor skill of student are not yet improve optimally. So, there isneeded applying of 3M activity. This research has a purpose to know the influence of3M activity. This research of applying 3M activity toward fine motor skill of 5-6 yearsold children in Education 21 Kindergarten Kulim of Pekanbaru City. Sample of thisresearch are 20 student of class K-2 Purple. Technique to college data is usingobservation technique and technique of data analysis is using t-test with using SPSS18.0 program. Hypotheses of this research is there are very significant influence towardstudent fine motor skill after applying 3M activity. This is knowing from the result ofdata obtained t=13,330 p=0,000 because p < 0,05. So, it can be conclude that there hasa very significant different of student fine motor skill. Fine motor skill after using 3Mactivity in teaching learning. So, its mean that Ho refused and Ha accepted that meansthere are very significant different between before and after doing the experiment with3M activity. The effect of 3m activity to fine motor skill of 5-6 years old children ateducation 21 kindergarten kulim of pekanbaru city as much as 33.21%.Keywords : Fine Motor Skill, 3M Activity